Progesterone and ultrasonographic changes during aglepristone or cloprosternol treatment in queens at 21 to 22 or 35 to 38 days of pregnancy - García Mitacek, María Carla (2017)
Progesterone (P4) is a requirement for pregnancy development. Previous reports observed a maximal value of serum P4 concentration on 21 days after the first mating after which it slowly declines throughout the rest of pregnancy. Ultrasound examination should be performed to ensure that pregnancy interruption is complete. Limited information is available on the ultrasonic appearance of conceptuses during pregnancy termination in cats The objective was to study serum P4 concentration and ultrasonographic changes during aglepristone (ALI) or cloprostenol (CLO) treatment and to evaluate the fertility after treatment. Two experiments (EXP) were carried out to accomplish this aim. Sixty queens, 12- to 36-month-old, were used. On Days 21 to 22 of pregnancy (EXP I) or 35 to 38 of pregnancy (EXP II), queens were divided into three groups (G). Queens in G1 received ALI (10 mg/kg, sc; EXP I, n = 10; EXP II, n = 10) for 2 consecutive days. Queens in G2 received CLO (5 μg/kg, sc; EXP I, n = 10; EXP II = 10) for 3 consecutive days. Queens in G3 received 1 mL of saline solution (PLA, sc; EXP I, n = 10; EXP II = 10). Blood samples were taken before treatment (Day 0) and every day during 10 days after the treatment to measure serum P4 concentrations. Likewise, after treatment, queens were monitored daily by ultrasonography for 10 days and weekly until the end of gestation to obtain gestational sacs measurements (GS), fetal measurements, and fetal biophysical profile. Data were analyzed by ANOVA. Serum P4 concentrations were significantly different on Day 6 (EXP I) and on Day 1 (EXP II) in ALI and CLO groups compared with PLA group (P < 0.05 and P < 0.01; respectively). The ultrasonographic monitoring during treatment allowed assessing changes in the GS and fetal measurements, embryo-fetal viability, and risk of pregnancy loss. In conclusion, the results from this study reported changes in serum P4 concentration and in ultrasonography measurements during pregnancy interruption with ALI or CLO treatment. Also it was observed that ALI and CLO are safe drugs and can preserve posttreatment queen fertility. Therefore, the results obtained in our work will be applied in feline reproduction practice.